Dependence of Si-29 NMR chemical shielding properties of precursor silicate species, Q(0) on its local structure at the pre-nucleation stages of zeolite synthesis - a DFT based computational correlation - Selvaraj, Kaliaperumal; Kurian, Reshmi (Microporous and Mesoporous Materials, 2009)
The exploration for new zeolite structures with tailored framework architectures for enhanced catalytic applications requires the knowledge about their nucleation and crystallization at molecular level. Nuclear magnetic resonance (NMR) is one of the most widely tried techniques to understand this. However, by NMR, it is difficult to accurately assign the molecular level precursor silicate structures at the pre-nucleation stages of zeolite synthesis. Hence, understanding the chemical shielding of such precursor molecules using quantum mechanical (QM) computations is extremely useful. Alkali is a fundamental component in the alkali based hydrothermal zeolite synthesis and its nature plays a major role. In the present report, we attempt to understand the differences in the local structure of the primary building block such as Si(OH)(4) (Q(0) silicate species) due to the associated alkali and their influence on NMR chemical shielding properties. Present work reports the calculation of Si-29 NMIR isotropic chemical shifts of T species with different cations such as Na, K and Ca using density functional theory (DFT). Results of natural bonding orbital (NBO) analysis, Perturbation theory energy analysis and electron density iso-surfaces were employed to obtain a deeper insight about their influence on the chemical shielding and on zeolite synthesis. (C) 2009 Elsevier Inc. All rights reserved.
Keywords: Ab initio method; Density Functional Theory (DFT); Electron density; NBO analysis; Perturbation theory; Q(0) silicate species; Si-29 NMR chemical shift; synthesis; zeolite

Convenient approach to the synthesis of different types of schiff's bases and their metal complexes - Pradhan, Kiran; Selvaraj, Kaliaperumal; Nanda, Ashis K. (Chemistry Letters, 2010)
Various metal complexes derived from different Schiff bases are conveniently prepared using solvent-free condensation reactions in one-pot synthesis, resulting in significantly enhanced yields Initial calorimetric studies, and/or TGA of reaction mixtures, led to better optimization of reaction conditions The ligands like mines, hydrazones, semicarbazones, and nitrones are also synthesized by this method, thus this process is general and expedient

Transformation of chemically fine tuned zeolite A precursor into dense lithium aluminosilicates - a comprehensive phase evolution and sintering study - Selvaraj, Kaliaperumal (Microporous and Mesoporous Materials, 2010)
Beyond their conventional revelation as catalysts, zeolites are being perceived as more challenging materials for modern applications. Thermal recrystallization of zeolite precursors is an efficient method for the preparation of dense aluminosilicate ceramics. However, factors viz., nature of the precursor and the way of firing it etc., influence the product quality. The present report is a systematic and detailed account of a phase transformation of Li modified zeolite A precursor using powder X-ray diffraction (PXRD), thermogravimetry (TG), differential thermal analysis (DTA), scanning electron micrographs (SEM), atomic absorption spectroscopy (MS), energy dispersive X-ray (EDX) and density measurement techniques. It involves an amorphisation followed by a recrystallization into lithium aluminosilicate (LAS). A comprehensive correlation of PXRD, TG/DTA, SEM, EDX and density data explains the complexity of high temperature phase transition (25-1200 degrees C). A qualitative phase analysis revealed the mediation of formation of LAS ceramic, beta-spodumene by few satellite transitions of SiO(2). (C) 2010 Elsevier Inc. All rights reserved.
Keywords: LAS silicate; Phase evolution; Phase transformation; Powder XRD; zeolite

Biogenic synthesis of silver nanoparticles using nicotiana tobaccum leaf extract and study of their antibacterial effect - Prasad, Kumar Suranjit; Pathak, Darshit; Patel, Ankita; Dalwadi, Palak; Prasad, Ram; Patel, Pradip; Selvaraj, Kaliaperumal (African Journal of Biotechnology, 2011)
A green synthesis of silver nanoparticle was carried out using tobacco leaf extract. Synthesized nanoparticles were characterized using UV-Vis absorption spectroscopy, TEM, EDAX, FT-IR and photoluminescence study, respectively. UV-Vis absorption spectroscopy of prepared silver colloidal solution showed absorption maxima at 418 nm. Excitation maximum and emission maximum obtained from photoluminescence study were found at 414 and 576 nm, respectively. TEM analysis showed average particle size of 8 nm, while SAED pattern confirmed the crystalline nature of synthesized nanoparticles. FT-IR analysis indicated the involvement of carboxyl (-C = O), hydroxyl (-OH) and amine (-NH) functional groups of tobacco leaf extract in preparation of silver nanoparticles. EDAX analysis showed proportion of silver (54.55%) among other elements in nanoparticle. Pseudomonas aeruginosa and Escherichia coli DH5 alpha showed highest sensitivity towards silver nanoparticles.
Keywords: FT-IR spectroscopy; photoluminescence; silver nanoparticles; Tobacco; UV-Vis absorption

Biosynthesis of Se nanoparticles and its effect on UV-induced DNA damage - Prasad, Kumar Suranjit; Patel, Hirnee; Patel, Tirtha; Patel, Khusbu; Selvaraj, Kaliaperumal (Colloids and Surfaces B-Biointerfaces, 2013)
This paper reports, an environmentally benign procedure of synthesis and characterizations of selenium nanoparticles and their protective effect against UV-induced DNA damage activities. An aqueous leaf extract of lemon plant was used as a precursor for synthesis of colloidal selenium nanoparticles. Resulting nanoparticles were characterized using UV-vis spectrophotometer, photoluminescence, TEM, EDAX, FT-IR and XRD, respectively. Selenium colloidal solution exhibited an absorption maximum at 395 nm and produced an emission maximum at 525 nm. Transmission electron microscopy followed by selected area electron diffraction pattern analysis indicated the formation of spherical, polydispersed, crystalline, selenium nanoparticles of diameter ranging from (similar to 60 to 80 nm). X-ray diffraction studies showed the formation of 111, 2 0 0 and 220 planes of face-centered cubic (fcc) selenium. EDAX analysis confirmed the presence of selenium in nanosphere. Fourier transformed infrared spectroscopic investigation reveled the involvement of carboxyl (-C=0), hydroxyl (-OH), amine (-NH) functional group of lemon plant extract in preparation of selenium nano particles. MU assay as well single cell gel electrophoresis assay or comet assay revealed that synthesized selenium nanoparticles, caused less cell death of lymphocytes and prevented DNA damage, when cells were exposed to UVB. The fluorescent property of selenium nanopartides can be used as diagnostic agent. Further, their anti DNA damaging property can be investigated as a chemotherapeutic agent in cancer therapy. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Comet assay; EDAX; FT-IR; MTT assay; Selenium nanoparticles; UV-vis spectrophotometer

Novel vanadium n-propylamino phosphate catalyst: synthesis, characterization and applications - Anumula, Rajini; Nookaraju, Muralasetti; Selvaraj, Kaliaperumal; Reddy, Ingala Ajit Kumar; Narayanan, Venkatathri (Materials Research-Ibero-American Journal of Materials, 2013)
A novel, lamellar type Vanadium n-propylamino phosphate catalyst is synthesized and characterized by using various physicochemical techniques such as Powder X-ray diffraction, Scanning electron microscopy/Energy dispersive X-ray analysis, Thermogravimetry/Differential thermal analysis, Fourier transform Infrared analysis, Electron spin resonance spectroscopy, Ultraviolet - Visible Diffuse reflectance spectroscopy, X-ray Photoelectron spectroscopy, P-31 Magic angle spinning Nuclear Magnetic Resonance spectroscopy and Catalytic applications toward Octahydroquinazolinone synthesis. It is found that the n-propylamine is present as sandwich between Vanadyl phosphate layers. Most of the Vanadium is present as V4+ ions in tetrahedral co-ordination. Vanadium n-propylamino phosphate catalyses Octahydroquinazolinone synthesis more effeciently and the optimum conditions required for Octahydroquinazolinone synthesis are, Benzaldehyde (2 mmol), Dimedone (2 mmol), Urea (4 mmol), Methanol + Water (1:1, 5 mL) and Catalyst (0.05 g). A plausible mechanism is also proposed.
Keywords: n-propylamino phosphate; octahydroquinazolinones; synthesis; Vanadium

Biogenic synthesis of selenium nanoparticles and their effect on as(III)-induced toxicity on human lymphocytes - Prasad, Kumar Suranjit; Selvaraj, Kaliaperumal (Biological Trace Element Research, 2014)
{A bioreductive capacity of a plant, Terminalia arjuna leaf extract, was utilized for preparation of selenium nanoparticles. The leaf extract worked as good capping as well as stabilizing agent and facilitated the formation of stable colloidal nanoparticles. Resulting nanoparticles were characterized using UV-Vis spectrophotometer, transmission electron microscopy (TEM), energy dispersive X-ray analysis (EDAX), Fourier transform infrared spectroscopy (FT-IR), and X-ray diffraction analysis (XRD), respectively. The colloidal solution showed the absorption maximum at 390 nm while TEM and selected area electron diffraction (SAED) indicated the formation of polydispersed, crystalline selenium nanoparticles of size raging from 10 to 80 nm. FT-IR analysis suggested the involvement of O-H, N-H
Keywords: Arsenite; Comet assay; EDAX; MTT assay; Selenium nanoparticles; Terminalia arjuna

Defluoridation using biomimetically synthesized nano zirconium chitosan composite: kinetic and equilibrium studies - Prasad, Kumar Suranjit; Amin, Yesha; Selvaraj, Kaliaperumal (Journal of Hazardous Materials, 2014)
{The present study reports a novel approach for synthesis of Zr nanoparticles using aqueous extract of Aloe vera. Resulting nanoparticles were embedded into chitosan biopolymer and termed as CNZr composite. The composite was subjected to detailed adsorption studies for removal of fluoride from aqueous solution. The synthesized Zr nanoparticles showed UV-vis absorption peak at 420 nm. TEM result showed the formation of polydispersed, nanoparticles ranging from 18 nm to 42 nm. SAED and XRD analysis suggested an fcc (face centered cubic) Zr crystallites. EDAX analysis suggested that Zr was an integral component of synthesized nanoparticles. FT-IR study indicated that functional group like -NH
Keywords: Aloe vera; Chitosan; FT-IR spectroscopy; Sorption; Zirconium nanoparticles

Synthesis of green nano iron particles (GnIP) and their application in adsorptive removal of As(III) and As(V) from aqueous solution - Prasad, Kumar Suranjit; Gandhi, Pooja; Selvaraj, Kaliaperumal (Applied Surface Science, 2014)
{The present study reports a new approach to synthesise nano iron particles using leaf extract of Mint (Mentha spicata L.) plant. The synthesised GnIPs were subjected to detailed adsorption studies for removal of arsenite and arsenate from aqueous solution of defined concentration. Iron nanoparticles synthesised using leaf extract showed UV-vis absorption peaks at 360 and 430 nm. TEM result showed the formation of polydispersed nanoparticles of size ranging from 20 to 45 nm. Nanoparticles were found to have core-shell structure. The planer reflection of selected area electron diffraction (SAED) and XRD analysis suggested that iron particles were crystalline and belonged to fcc (face centred cubic) type. Energy-dispersive X-ray analysis (EDAX) shows that Fe was an integral component of synthesised nanoparticles. The content of Fe in nanoparticles was found to be 40%, in addition to other elements like C (16%), 0 (19%) and Cl (23%). FT-IR study suggested that functional groups like NH
Keywords: Adsorption; Arsenate; Arsenite; Iron nanoparticles; kinetics; M. spicata L.

Efficient sorption and photocatalytic degradation of malachite green dye onto NiS nanoparticles prepared using novel green approach - Prasad, Kumar Suranjit; Prajapati, Sheel; Selvaraj, Kaliaperumal (Korean Journal of Chemical Engineering, 2015)
The extract of the Asparagus racemosus leaf tissue works as a stabilizing and capping agent and assists the formation of stable colloidal nanoparticles. Nanoparticles were characterized using UV-vis spectrophotometer, photoluminescence, TEM, EDAX and XRD, respectively. Transmission electron microscopy followed by selected area electron diffraction pattern analysis indicated the formation of near spherical, polydispersed, crystalline NiS of diameter ranging from 4-27 nm. X-ray diffraction studies showed the formation of 110, 101, 300, 021, 220, 221, 131, 410, 401, 321, 330 and 021 planes of hexagonal NiS. EDAX analysis confirmed the presence of Ni and S in nanosphere. The maximum sorption capacity (q (m) ) of NiS nanoparticles for MG dye was found to be 64.85 mg/g. Decolorization as well as disintegration of malachite green under white light illumination was confirmed by LC-MS studies. Results of the present study suggest that nanosized NiS can play an instrumental role in photocatalytic degradation of malachite green dye present in water bodies.
Keywords: Degradation; FTIR; Malachite Green; NiS Nanoparticles; TEM

Microbial selenium nanoparticles (SeNPs) and their application as a sensitive hydrogen peroxide biosensor - Prasad, Kumar Suranjit; Vaghasiya, Jayraj V.; Soni, Saurabh S.; Patel, Jitesh; Patel, Rinkesh; Kumari, Madhu; Jasmani, Falguni; Selvaraj, Kaliaperumal (Applied Biochemistry and Biotechnology, 2015)
The cell-free extract, a crude enzyme (cytosolic and membrane fraction) obtained from an environmental isolate, Bacillus pumilus sp. BAB-3706 worked as excellent in reducing as well as stabilizing agent and facilitated the formation of stable colloidal selenium nanoparticles (SeNPs). Resulting nanoparticles were characterized using UV-vis spectrophotometer, TEM, EDAX, FT-IR and XRD, respectively. A working electrode was modified by coating the surface of indium tin oxide (ITO) with colloidal SeNPs. Successive additions of H2O2 (100 to 600 mu M) in conventional three electrodes system, cyclic voltammeter with potential scan rate 25.0 mV/s, in 0.1 M phosphate buffer solution (PBS) yielded increase in current. A perpetual amperometric response at fixed potential (-1.0 V) and at selected time interval of 100 s showed different magnitude of current at every addition of H2O2. The linear range of detection of H2O2 was from 5 to 600 mM (R (2) = 0.9965), while the calculated limit of detection was found to be 3.00 mu M. The current study suggested that microbial SeNPs can be used for fabrication of low cost, sensitive H2O2 biosensor.
Keywords: Biosensor; EDAX; Hydrogen peroxide; Selenium nanoparticles; TEM; UV-vis spectroscopy

Non-templated ambient nanoperforation of graphene: a novel scalable process and its exploitation for energy and environmental applications - Jhajharia, Suman Kumari; Selvaraj, Kaliaperumal (Nanoscale, 2015)
Nano-perforation of 2D graphene sheets is a recent and strategically significant means to exploit such materials in modern applications such as energy production and storage. However, current options for the synthesis of holey graphene (hG) through nano-perforation of graphene involve industrially undesirable steps viz., usage of expensive/noble metal or silica nanoparticle templates and/or hazardous chemicals. This severely hampers its scope for large scale production and further exploitation. Herein, we report for the first time a scalable non-templated route to produce hG at ambient conditions. Nano-perforation is achieved with tunable pore size via the simple few layer co-assembly of silicate-surfactant admicelles along the surface of graphene oxide. A gentle alkali treatment and a reduction at optimized conditions readily yielded holey graphene with a remarkable capacitance (similar to 250 F g(-1)) and interesting adsorption abilities for pollutants. Density functional theory based computational studies reveal interesting insights on the template free nano-perforation at a molecular level. This simple rapid process not only excludes the need for expensive templates and harmful chemicals to yield hG at attractively ambient, chemically placid and industrially safer conditions, but also creates no hurdles in terms of scaling up.

Bioresponsive carbon nano-gated multifunctional mesoporous silica for cancer theranostics - Prasad, Rajendra; Aiyer, Sandhya; Chauhan, Deepak S.; Srivastava, Rohit; Selvaraj, Kaliaperumal (Nanoscale, 2016)
Designing bioresponsive nanocarriers for controlled and efficient intracellular drug release for cancer therapy is a major thrust area in nanomedicine. With recent recognition by the US FDA as a safe material for human trials, mesoporous silica nanoparticles (MSNPs) are being extensively explored as promising theranostic agents. Green fluorescent carbon quantum dots (CQDs), though known as possible alternatives for their more toxic and relatively less efficient predecessors, are less known as gate keepers for drug release control. We report for the first time an efficient bioresponse of CQDs when judiciously designed using glutathione cleavable (redox responsive) disulphide bonds. When the anticancer drug doxorubicin loaded MSNPs are capped with these CQDs, they display promising drug release control on exposure to a mimicked intracellular cancer environment. Their dual functionality is well established with good control on preventing the premature release and exceptional bio-imaging of HeLa cancer cells. Fluorescence images prove selective targeting of HeLa cells by overexpression of folate receptors from the surface functionalised folic acid ligand. Extensive characterisation using XRD, TEM, BET analysis, drug loading tests, drug release kinetics, MTT assay and fluoroscence cell imaging helps in understanding the multi-functionalities of the successful design, extending its scope with exciting prospects towards non-invasive targeted drug delivery and bio-imaging for effective cancer diagnosis and treatment.

DFT based assay for tailor-made terpyridine ligand-metal complexation properties - Joshi, Krati; Krishnamurty, Sailaja; Singh, Iksha; Selvaraj, Kaliaperumal (Molecular Simulations, 2016)
Electron-rich terpyridine ligand and its metal complexes have a potential to grow as responsive surfaces by adapting their physicochemical properties as a function of environment. The responsiveness is brought about by judicious molecular level designing that is currently hindered due to lack of information and control on terpyridine (TPy)-metal (M) interactions at single molecule level. So far there is no organised understanding on the binding of different metals with TPy ligand and ways to modulate it. Being a large conjugated [GRAPHICS] system, TPy has a large scope to be functionalised with electron exchanging groups to alter its electronic structure and consequently its binding with metal atoms. In first report of such a kind, using density functional theory (DFT), we demonstrate that convenient modulation of TPy-M binding is possible through functionalisation of TPy for [GRAPHICS] , Ru, Fe, Mo and Au. Electron donating groups viz., CH [GRAPHICS] , OCH [GRAPHICS] , C [GRAPHICS] H [GRAPHICS] , NH [GRAPHICS] and electron withdrawing groups viz., CF [GRAPHICS] , COOH, CN and NO [GRAPHICS] are considered for functionalisation of TPy ligand. Significantly, the present work focuses on the functionalisation at 4 and 4 [GRAPHICS] positions of TPy molecule. The role of such a functionalisation in influencing the ligands structure-property correlation is missing in the literature to the best of our knowledge. The present investigation quantifies that by pertinent functionalisation of TPy, TPy-M binding energies can be modified up to [GRAPHICS] 60kcal/mol. Our results reveal that functionalisation leads to a considerable charge redistribution within the TPy-M complex with carbon atoms in pyridine rings functioning as major electron sink/source with a corresponding red/blue shift of [GRAPHICS] stretching frequency. This modifies the red-ox, optical and other chemical properties of TPy-M complexes. In brief, the present report illustrates a way to design ligands such as TPy for diverse applications through tailor-made functionalisation using electronic structure methodology.
Keywords: Binding energy; charge redistribution; Density functional theory; functionalisation; Metal organic complexes; metal-ligand interactions; terpyridine

PD@SBA-15 Nanocomposite catalyst: synthesis and efficient solvent-free semihydrogenation of phenylacetylene under mild conditions - Bhuyan, Diganta; Selvaraj, Kaliaperumal; Saikia, Lakshi (Microporous and Mesoporous Materials, 2017)
Pd-0 nanoparticles (NPs) have been fabricated on SBA-15 using a facile, rapid and highly reproducible microwave-assisted reduction by solvent method. The as-synthesized Pd@SBA-15 nanocomposite was well characterized using low angle and wide angle XRD, TEM, FE-SEM, N-2 adsorption-desorption isotherm, FTIR, XPS etc. The Pd@SBA-15 nanocomposite act as an active, recyclable heterogeneous catalyst for semihydrogenation of phenylacetylene under solvent-free mild reaction conditions (303 K, atmospheric H-2). A maximum of 94.4% phenylacetylene conversion was achieved with very high selectivity for styrene (95.5%). Moreover, the used catalyst was recovered by centrifugation and reused up to four times without significant loss in their catalytic activity. This optimized reaction protocol for phenylacetylene was also well performed in case of various other alkynes with similar or better performance. (C) 2016 Elsevier Inc. All rights reserved.
Keywords: Pd-0 nanoparticles; Phenylacetylene; SBA-15; Semihydrogenation; Solvent-free

Redox-mediated 3D graphene based nanoscoop design for ultracapacitor applications - Rani, Pallavi; Jhajharia, Suman Kumari; Selvaraj, Kaliaperumal (New Journal of Chemistry, 2017)
Contemporary energy storage devices significantly rely on the rational design of micro and nanostructural features of electrode materials for efficient ion transport. A judicious concept of utilizing the extended charge mobility on the third dimension along with an active redox couple to significantly maximize the capacitance has been demonstrated via (a) the fabrication of a 3D network from 2D graphene and (b) the introduction of an active redox species. Compared with traditional graphene systems, an unprecedented 8-fold gain of capacitance that was sustained with minimal loss even beyond 5000 cycles is achieved and is reported for the first time. This was due to the complementary advantage of both the electric double layer capacitance of the 3D graphene electrode and the redoxmediated pseudocapacitance of K3Fe(CN)(6) in alkaline electrolytes. Colloidal polystyrene spheres with a tunable size range were used as sacrificial templates for generating the 3D network. This design outperforms others, is an excellent candidate as an ultracapacitor and is envisaged to lead to new opportunities in several electrochemical applications.

Synthesis of water soluble CdS nanoparticles and study of their DNA damage activity - Prasad, K. S.; Amin, T.; Katuva, S.; Kumari, Madhu; Selvaraj, Kaliaperumal (Arabian Journal of Chemistry, 2017)
This study reports a novel method for preparation of water soluble CdS nanoparticles using leaf extract of a plant, Asparagus racemosus. The extract of the leaf tissue which worked as a stabilizing and capping agent, assisted the formation of nanoparticles. Nanoparticles were characterized using a UV–vis spectrophotometer, Photoluminescence, TEM, EDAX, XRD and FT-IR. Transmission electron microscopy followed by selected area electron diffraction pattern analysis indicated the formation of spherical, polydispersed, crystalline, CdS of diameter ranging from 2 to 8 nm. X-ray diffraction studies showed the formation of 1 1 1, 2 2 0 and 3 1 1 planes of face-centered cubic (fcc) CdS. EDAX analysis confirmed the presence of Cd and S in nanosphere. The cytotoxicity test using MTT assay as well as DNA damage analysis using comet assay revealed that synthesized nano CdS quantum dots (QDs) caused less DNA damage and cell death of lymphocytes than pure CdS nanoparticles.

Disintegrable NIR light triggered gold nanorods supported liposomal nanohybrids for cancer theranostics - Chauhan, Deepak S.; Prasad, Rajendra; Devrukhkar, Janhavi; Selvaraj, Kaliaperumal; Srivastava, Rohit (Bioconjugate Chemistry, 2018)
In this work, facile synthesis and application of targeted, dual therapeutic gold nanorods-liposome (GNR-Lipos) nanohybrid for imaging guided photothermal therapy and chemotherapy is investigated. The dual therapeutic GNR-Lipos nanohybrid consists of GNR supported, and doxorubicin (DOX) loaded liposome. GNRs not only serve as a photothermal agent and increase the drug release in intracellular environment of cancer cells, but also provide mechanical strength to liposomes by being decorated both inside and outside of bilayer surfaces. The designed nanohybrid shows a remarkable response for synergistic chemophotothermal therapy compared to only chemotherapy or photothermal therapy. The NIR response, efficient uptake by the cells, disintegration of GNR-Lipos nanohybrid, and synergistic therapeutic effect of photothermal and chemotherapy over breast cancer cells MDA-MB-231 are studied for the better development of a biocompatible nanomaterial based multifunctional cancer theranostic agent.

In vivo examination of folic acid-conjugated gold-silica nanohybrids as contrast agents for localized tumor diagnosis and biodistribution - Prasad, Rajendra; Agawane, Sachin B.; Chauhan, Deepak S.; Srivastava, Rohit; Selvaraj, Kaliaperumal (Bioconjugate Chemistry, 2018)
Enhanced biocompatibility of nanosized contrast agent with high radiodensity and specific biodistribution is an important parameter for localized tumor imaging and organ safety. Various nanoparticles, especially gold nanorods (GNRs), have been applied for tumor diagnosis. However, their toxicity, nonspecific biodistribution, and easy aggregation are critical issues in cancer medicine. To avoid these issues, encapsulation of the GNRs in the core of nanoscopic mesoporous silica (MS) under ambient conditions, yielding multifunctional nanomaterials for cancer nanomedicine, is a recent and active development. Interestingly, GNR embedded MS nanohybrid (GNR-MS), though a promising material in nanomedicine, is rarely examined for tumor diagnosis, in vivo toxicity, organ safety, contrast ability, and excretion. Herein, we report a systematic in vivo examination of folic acid functionalized GNR-MS (GNR-MS-FA) for localized 4T1 breast tumor diagnosis, organ safety, and excretion using a one-time dose administration. The nanomaterials show good aqueous dispersibility, biocompatibility, high radiodensity, and tumor specific targeting ability (in vitro as well as in vivo). The in vivo tumor diagnosis and specific biodistribution of injected nanomaterials clearly demonstrates their potential for the visualization of tumors deep in the body of mice. In addition, all organs including the healthy glomerulus of the kidney are observed to be free of tissue injuries thereby indicating the superior biocompatibility of the nanomaterials.

Dinitrogen activation on graphene anchored single atom catalysts: local site activity or surface phenomena - Maibam, Ashakiran; Govindaraja, Thillai; Selvaraj, Kaliaperumal; Krishnamurty, Sailaja (Journal of Physical Chemistry C, 2019)
Catalysis on two-dimensional (2D) substrates with metal clusters or centers is generally dealt with as a surface phenomenon under the conjecture that the delocalized electron density is the driving force. When single atom catalysts (SACs) are anchored on such materials with delocalized electron density, for instance graphene, the stimulant for catalysis may be either the d-electrons on the metal or the system altogether. To understand the contributing factors of catalysis on such systems, a case study of dinitrogen (N-2) activation on Mo anchored graphene has been made by employing periodic and finite models of graphene. The periodic model represents a continuum of SACs anchored periodically on graphene, while the finite models are graphene nanoflakes of varying sizes and edge orientations. In addition to the physical aspects, such as size/finiteness of graphene, the influence of varying chemical compositions of the substrate on the activity is also evaluated by doping graphene with different B and N concentrations. This study, while clearly bringing out the connotation of regulating atomic composition of graphene substrate for dinitrogen activation, also surprisingly unveils the relative insignificance of varying the size and edge effects of the substrate. These features are highlighted through an analysis of red shift in the N-N stretching frequency, charge transfer to dinitrogen from the catalytic system, and structural and electronic characteristics of the catalytic system. The total and projected density of states plots reveal hybridization between the metal d orbitals and the p orbitals of carbon and nitrogen in the valence band. On the other hand, the frontier molecular orbital analysis also depicts a strong chemisorption of dinitrogen with the metal-graphene supports on account of direct hybridization between the d orbitals of the supported metal atom and the p orbitals of dinitrogen. The Bader and Lowdin charge distribution on the adsorbed dinitrogen in periodic and finite models shows the preeminence of local site over the surface activity.

Exploring battery-type ZnO/ZnFe2O4 spheres-3D graphene electrodes for supercapacitor applications: advantage of yolk-shell over solid structures - Jhajharia, Suman Kumari; Manappadan, Zinoy; Selvaraj, Kaliaperumal (ChemElectroChem, 2019)
Recently, a ZnO/ZnFe2O4 composite has been reported to be a promising material for energy storage, owing to its large specific capacity and good redox activity. However, due to the inability to accommodate its strong volumetric variations during operation, it fails to retain its capacitance, which remains as a significant hitch. Herein, we present our attempt towards solving this through a binder-free electrode design comprising a porous yolk-shell ZnO/ZnFe2O4 composite matrixed inside a 3D network of graphene, which, in turn, is grown on Ni foam. The design exhibits a four-fold increase in its specific capacitance, yielding 1334 F g(-1) (specific capacity of 370.5 mAh g(-1)) at a current density of 0.5 A g(-1) in comparison to that of the ZnO/ZnFe2O4 electrodes (309 F g(-1) (85.8 mAh g(-1)) at 0.5 A g(-1)) comprising solid metal oxide spheres. The major advantage of the design is the well-defined yolk-shell architecture that provides free space for volume expansion during long cycling processes and channels for ionic transportation; whereas, the conductive 3D graphene network and porous Ni foam facilitate electronic conduction. The availability of free space in yolk-shell sphere electrodes facilitates the capacitance retention of up to 80 % beyond 5000 cycles at a current density of 1 A g(-1), which is in contrast to the capacitance retained by the solid spheres of only approximately 60 %. These results directly demonstrate the significant consequence of the yolk-shell architecture-based binder-free design and its promising potential in high-performing supercapacitors and batteries.
Keywords: binder-free electrodes; graphene hydrogels; Supercapacitors; volume expansion; yolk-shell spheres

Graphene oxide supported liposomes as red emissive theranostics for phototriggered tissue visualization and tumor regression - Prasad, Rajendra; Yadav, Amit S.; Gorain, Mahadeo; Chauhan, Deepak S.; Kundu, Gopal C.; Srivastava, Rohit; Selvaraj, Kaliaperumal (ACS Applied Bio Materials, 2019)
Selective tissue visualization and localized tumor regression without affecting the surrounding healthy tissues are critical concerns in cancer nanomedicine. Importantly, the complete wrapping of a flimsy matrix like liposome by multifunctional graphene oxide is an interesting engineering idea for nanomedicine design. Moreover, designing a safe and biodegradable nanohybrid with significant theranostic ability is a current need for targeted combined therapies. Here, we report a comprehensive result of in vivo tumor diagnosis and phototriggered tumor regression using a biodegradable red emissive nanotheranostic system, viz., graphene oxide flakes fortified liposome (GOF-Lipo), functionalized with folic acid (FA): GOF-Lipo-FA. Graphene oxide support enhances the stability of drug-loaded liposomes in an extracellular environment that prevents the premature release of loaded anticancer drug from the liposomal cavity. Promising outcomes of tumor regression (∼300 to 25 mm3) from organized cellular and animal studies are demonstrated in this work. These studies reveal superior biocompatibility, deep intracellular localization, 4T1 breast tumor diagnosis, and long time tumor binding ability of an injected emissive nanohybrid. Overall, a single dose of designed multifunctional systems demonstrates the best tumor regression.

Removal of fluoride from aqueous solution by mesoporous silica nanoparticles functionalized with chitosan derived from mushroom - Srivastava, Anushree; Kumari, Madhu; Ramanathan, Alagappan; Selvaraj, Kaliaperumal; Prasad, Bablu; Prasad, Kumar Suranjit (Journal of Macromolecular Science Part A-Pure and Applied Chemistry, 2020)
In the present study, chitosan functionalized mesoporous silica nanoparticles have been synthesized. Chitosan derived from an edible mushroom, Agaricus bisporus was used during synthesis of chitosan functionalized silica nanoparticles. The functionalized silica nanoparticles were subjected to fluoride sorption using a batch method which subsequently showed removal efficiency of 95% with maximum sorption capacity, 58.8 mg/g. The characterization of nanoparticles was carried out by SEM, EDAX, XRD and FTIR analysis respectively. EDAX analysis suggested that oxygen, 51.83% and silica 37.24% was main constituent of the functionalized nanomaterials. XRD yielded characteristic diffraction pattern corresponding to the lattice planes (100), (110), (112), (120), (200) and (220) respectively. Sorption data was used to study equilibrium isotherm namely Langmuir and Freundlich model. The adsorption capacity increased with temperature while kinetics studies revealed that the adsorption process followed a pseudo-second-order rate equation. The enthalpy change (Delta H) and entropy change (Delta S) was found to be -31.36 kJmol(-1) and -7.75 Jmol(-1) K-1, showing endothermic and spontaneous nature of the fluoride adsorption. Data suggested that the nature of adsorption belonged to chemisorptions. The overall results suggested that the synthesized nanoparticles showed strong and specific affinity for fluoride and could be excellent adsorbents for defluoridation.
Keywords: Adsorption; Chitosan; EDAX; Fluoride; SEM

Unravelling the distinct surface interactions of modified graphene nanostructures with methylene blue dye through experimental and computational approaches - Manappadan, Zinoy; Kumar, Shubham; Joshi, Krati; Govindaraja, Thillai; Krishnamurty, Sailaja; Selvaraj, Kaliaperumal (Journal of Hazardous Materials, 2020)
Nanoscopic modifications leading to multi-dimensional graphene structures are known to significantly influence their candidature for several applications including catalysis, energy storage, molecular sensing and most significantly adsorption and remediation of harmful materials such as dyes. The present work attempts to identify the key trajectories that connect the structural qualification with a chosen application, viz., the interactive forces in dye remediation. Various physico-chemically Modified Graphene Nanostructures (MGNs) such as 2 dimensional Graphite, Graphene Oxide (GO), reduced GO (rGO), holey rGO, and 3 dimensional GO hydrogel and Holey GO hydrogel are chosen and synthesised herein. These represent varieties of physicochemical features with respect to their dimensionality, surface features such as oxygen functionality, nanoscopic holes etc., that contribute to their characteristic overall surface interactions. Methylene Blue (MB), a popular industrial effluent posing major environmental concern is chosen to be a probe adsorbate in this case study. An exclusive real time in-situ UV visible spectral experiment provides the revealing reasons behind the outstanding performance of 2D GO sheets with an adsorption capacity of greater than 92 % even at high MB concentrations (>2000 ppm). A complex dependency of various factors such as surface oxygen, morphology, nanoporosity etc. on the unique overall interaction with an adsorbent such as MB by all these adsorbates is demonstrated using experimental and DFT based computational studies. Electrostatics and hydrogen bonding are understood to be the two dominant forces driving the MB adsorption on the best performing GO here.
Keywords: Density functional theory; In-situ UV-vis spectroscopy; Interactions; Methylene blue; Modified Graphene Nanostructures

Molecularly engineered graphene oxide anchored metal organic assembly: an active site economic bi-functional electrocatalyst - Jhajharia, Suman Kumari; Selvaraj, Kaliaperumal (FlatChem, 2021)
Low-temperature fuel cells are the most promising sustainable energy technology as they use hydrogen, an environmentally clean fuel. However, the sluggish kinetics of oxygen electrochemistry, a chronic issue, is holding them from commercialization. Herein, we address this issue through a molecular level design of a Graphene oxide anchored Metal Organic Molecular Assembly (G-MOMA) based catalyst. This non-precious metal catalyst consists of Ni and Fe ions ligated by graphene oxide supported terpyridine, a unique molecular assembly design that maximizes the utilization of active metal centers. This G-MOMA catalyst brings down an over potential (240 mV) for oxygen evolution reaction (OER) as close as that of the bench mark catalyst Ru/C with an impressive Tafel slope of 58 mV/dec and a cyclic stability of >30,000 cycles. G-MOMA excels in oxygen reduction reaction (ORR) too with an onset at 0.88 V (vs RHE). The remarkably stable G-MOMA catalyst surprises with an excellent bi-functionality towards both OER and ORR with an overall potential difference of mere 0.77 V, which is 180 mV and 70 mV lesser than the standard Pt/C and Ru/C catalysts, respectively. The G-MOMA catalyst is well in the activity range of the state-of-art bi-functional catalysts and yet cheaper by many folds.
Keywords: Bi-functional electrocatalyst; graphene oxide; Metal organic molecular assembly; Oxygen Evolution Reaction; oxygen reduction reaction; terpyridine

Electrochemically tuned synergistic nano-interface of a tertiary Ni(OH)(2)-NiO(OH)/NixP heterojunction material for enhanced and durable alkaline water splitting - Manappadan, Zinoy; Selvaraj, Kaliaperumal (ChemistrySelect, 2022)
Making water splitting cheaper is the need of the hour.The present work reports a nickel-based, non-precious catalytic system, synthesized by a two-step electrodeposition (ED) process followed by a short-term heat treatment. The Ni(OH)(2)-NiO(OH)/NixP heterojunction has been synthesized and optimized through an unprecedented, energy-conserving method to achieve its best OER performance. Further, it has been carefully tuned for the first time by thoroughly optimizing the ED parameters to exhibit Hydrogen Evolution Reaction (HER). At high current regimes, the performance surpassed that of the Ru/C and Pt/C (>= 500 mA and >= 600 mA) respectively. The full cell electrolyzer configuring NOPO||NOPH further establishes the supremacy of the present electrocatalysts over the benchmark Ru/C||Pt/C. Moreover, the present electrocatalyst displayed 60 and 70 hours of HER and OER performances at -100 mA and 100 mA currents respectively. In short, this work is an example that illustrates how a single chemical system gets to exhibit two complementary catalytic behaviors that is, water oxidation and reduction when certain synthetic parameters are meticulously optimized.
Keywords: Electrodeposition; heterojunction; Ni(OH)(2)-NiO(OH); NixP; non-precious metal; water splitting

Can Li atoms anchored on boron- and nitrogen-doped graphene catalyze dinitrogen molecules to ammonia? a DFT study - Verma, Tushar Singh; Samal, Pragnya Paramita; Selvaraj, Kaliaperumal; Krishnamurty, Sailaja (ChemPhysChem, 2023)
The most successful electrochemical conversion of ammonia from dinitrogen molecule reported to date is through a Li mediated mechanism. In the framework of the above fact and that Li anchored graphene is an experimentally feasible system, the present work is a computational experiment to identify the potential of Li anchored graphene as a catalyst for N-2 to NH3 conversion as a function of (a) minimum number of Li atoms needed for anchoring on graphene sheets and (b) the role of chemical modification of graphene surfaces. The studies bring forth an understanding that Li anchored graphene sheets are potential catalysts for ammonia conversion with preferential adsorption of N-2 through end-on configuration on Li atoms anchored on doped and pristine graphene surfaces. This mode of adsorption being characteristic of Nitrogen Reduction Reaction (NRR) through enzymatic pathway, examination of the same followed by analysis of electronic properties demonstrates that tri-Li atoms (Tri Atom Catalysts, TACs) are more efficient as catalysts for NRR as compared to two Li atoms (Di Atom Catalysts, DACs). Either way, the rate determining step was found to be *NH2 ->*NH3 step (mixed pathway) with Delta G(max)=1.02 eV and *NH2-*NH3 ->*NH2 step (enzymatic pathway) with Delta G(max)=1.11 eV for 1B doped TAC and DAC on graphene sheet, respectively. Consequently, this work identifies the viability of Li anchored graphene based 2-D sheets as hetero-atom catalyst for NRR.
Keywords: computational chemistry; Graphene Sheet; heterogeneous catalysis; Li Nanoparticles; Nitrogen Reduction Reaction

Effective distribution of gold nanorods in ordered thick mesoporous silica: a choice of noninvasive theranostics - Prasad, Rajendra; Selvaraj, Kaliaperumal (ACS Applied Materials & Interfaces, 2023)
Porous silica coated gold nanorod core-shell structures demonstrate a multifunctional role in bioimaging, drug delivery, and cancer therapeutics applications. Here, we address a new approach for effective distribution of gold nanorods (GNRs) in a mesoporous silica (MS) shell, viz., one nanorod in one silica particle (GMS). We have studied that silica coating presents major advantages for the better biocompatibility and stability of GNRs. In this study, two different thicknesses of silica shell over GNRs have been discussed as per the application's need; GNRs in thin silica (11 nm) are fit for phototherapy and bioimaging, whereas thick and porous silica (51 nm) coated gold nanorods are suitable for triggered drug delivery and theranostics. However, effective distribution of GNRs in ordered architecture of thick mesoporous silica (MS, more than 50 nm thickness) with high surface area (more than 1000 m(2)/g) is not well understood so far. Here, we present methodical investigations for uniform and highly ordered mesoporous silica coating over GNRs with tunable thickness (6 to 51 nm). Judicious identification and optimization of different reaction parameters like concentrations of silica precursor (TEOS, 1.85-43.9 mM), template (CTAB, 0.9-5.7 mM), effect of temperature, pH (8.6-10.8), stirring speed (100-400 rpm), and, most importantly, the mode of addition of TEOS with GNRs have been discussed. Studies with thick, porous silica coated GNRs simplify the highest ever reported surface area (1100 m(2)/g) and cargo capacity (57%) with better product yield (g/batch). First and foremost, we report a highly scalable (more than 500 mL) and rapid direct deposition of an ordered MS shell around GNRs. These engineered core-shell nanoparticles demonstrate X-ray contrast property, synergistic photothermal-chemotherapeutics, and imaging of tumor cell (96% cell death) due to released fluorescent anticancer drug molecules and photothermal effect (52 degree celsius) of embedded GNRs. A deeper insight into their influence on the architectural features and superior theranostics performances has been illustrated in detail. Hence, these findings indicate the potential impact of individual GMS for image guided combination therapeutics of cancer.
Keywords: CombinationTherapy; Contrast Agent; Core-ShellStructure; GoldNanorods; Imaging; Mesoporous silica; Nanoparticles; TheranosticsIntervention

Computational identification of most potent atom pair catalysts for electrocatalytic nitrogen reduction reaction over hydrogen evolution reaction - Verma, Tushar Singh; Dar, Afshana Hassan; Dar, Manzoor Ahmad; Selvaraj, Kaliaperumal; Krishnamurty, Sailaja (Inter., 2024)
Robust electrocatalytic atom pair compositions (APCs) where Nitrogen Reduction Reaction (NRR) is more enhanced over competing Hydrogen Evolution Reaction (HER) is searched for using computational studies based on Density Functional Theory based methods. Atomic pairs are anchored on mechanically and thermally stable graphene surfaces. A wide range of transition metal based atom pair compositions from 3d, 4d, and 5d groups are systematically investigated for reduction of dinitrogen molecule with lower reduction barrier as compared to HER. APR compositions of Ni-Rh with an overall limiting potential of -0.22 V, Fe-W with an overall limiting potential of -0.26 V and Co-Pt with an overall limiting potential of -0.28 V are identified as the most potent atomic pairs for enhanced nitrogen reduction reaction over the HER. Finally, the performance of most potent composition, viz., Ni-Rh is validated to be consistent with respect to their thermodynamic stability and performance within the solvent effects.
Keywords: Atom pair catalysts; Density Functional Theory (DFT); Electrochemical nitrogen reduction reaction (eNRR); hydrogen evolution reaction (HER); IR stretching frequencies; N-N bond length

Nanocrystalline (NixCo(1-x))3(PO4)2@FeSe2/NF as a promising OER electrocatalyst for alkaline water electrolysis - Christi, Darren Sebastian; Selvaraj, Kaliaperumal (International Journal of Hydrogen Energy, 2024)
Affordable and sustainable hydrogen production is the need of the hour owing to the mounting global pursuit for the hydrogen economy. Water splitting is the premier go -to method to produce green hydrogen at a larger scale in which the half -cell Oxygen Evolution Reaction (OER) demands a larger amount of energy expenditure due to its sluggish kinetics. Hence, designing an efficient OER electrocatalyst, especially for alkaline water electrolysis that offers alternatives to the usage of precious group metals is a pressing priority. Herein, we report a novel nanocrystalline electrocatalyst consisting of two components, namely cobalt nickel phosphate and iron diselenide synthesised via a two-step electrodeposition at room temperature. The combination of the two components on the porous nickel foam substrate exhibits an overpotential of 272 mV at 100 mA/cm2 in 1 M KOH showing a low Tafel slope of a mere 38 mV/dec with appreciable retention even after 24 h of stability test at a relatively higher current density. The surface reconstruction that occurs when FeSe2 is electrodeposited on (Ni0.35Co0.65)3(PO4)2@NF and the synergy between the two components is the primary reason for the improved performance. Thus, this work highlights the ambient synthesis of a highly durable earth -abundant metal -based electrocatalyst which exceeds the performance of the standard Ru/C by a decent margin.
Keywords: Alkaline Water Electrolysis; Ambient synthesis; Electrodeposition; Non-PGM based Electrocatalyst; OER

Tensile nanostructured hierarchically porous non-precious transition metal-based electrocatalyst for durable anion exchange membrane-based water electrolysis - Singh, Kailash; Selvaraj, Kaliaperumal (Journal of Colloid and Interface Science, 2024)
Electrochemical water electrolysis is a promising method for sustainable hydrogen production while transiting towards hydrogen economy. Among many, the Anion Exchange Membrane (AEM) based water electrolyzer is an emerging yet potentially affordable technology on maturity for producing large-scale hydrogen accommodating the usage of Non-Platinum Group Metal (non-PGM) based inexpensive electrocatalysts. Herein, we demonstrate the excellent performance of a bifunctional Nickel Copper Phosphide-Nickel sulphide (NCP-NS) electrocatalyst with a unique tensile nanostructure obtained via a facile, controlled ambient galvanic displacement route. An AEM electrolyzer with a larger active area of 10 cm(2) stacked with the symmetric NCP-NS electrodes and a membrane demonstrates scalability with a requirement of a mere 1.66 V to reach a current density of 10 mA cm(-2). The nickel-copper phosphide boosts the kinetics of charge transfer between the electrode and electrolyte interface, while a unique combination of a few nickel sulphide phases present in the catalyst provides sufficiently appropriate active sites for the overall water electrolysis. For the first time, we report a room temperature performance of similar to 230 mA cm(-2) at 2 V for a non-PGM-based bifunctional electrocatalyst with exceptional durability for over 300 h of operation in an AEM water electrolyser with a retention rate of 95 %-97 % at a current density range of 80-800 mA cm(-2).
Keywords: AEM electrolyzer; Bifunctionality; Electrodeposition; Non-PGM based Electrocatalyst; stability

Effect of doping on electrocatalytic dehydrogenation and hydrogenation of methyl decalin-methyl naphthalene system - Verma, Tushar Singh; Selvaraj, Kaliaperumal; Krishnamurty, Sailaja (Journal of Physical Chemistry C, 2025)
The hydrogen economy can benefit from the use of liquid organic hydrogen carriers (LOHCs) for cross-continent hydrogen transportation in the future. However, dehydrogenation and hydrogenation of hydrogen require catalytic systems. Current research emphasizes selective Pt/Rh doping of Fe, Co, and Ni surfaces as catalysts for the dehydrogenation and hydrogenation of the methyl naphthalene-methyl decalin LOHC system, which has more than 7% hydrogen weight capacity and meets the practical requirements established by the European Union and the United States Department of Energy. Density functional theory-based computational techniques demonstrate how the chemical modification of these surfaces with a Pt and Rh single-atom catalyst (SAC) can improve the efficiency of dehydrogenation and hydrogenation. With a sustainable method, electrochemical dehydrogenation and hydrogenation on these robust surfaces produce effective hydrogen storage for extended periods without losing hydrogen. Furthermore, optimal results for the hydrogenation of 2-methyl naphthalene on Fe-Rh SAC with path-determining step (PDS) = 0.98 eV and dehydrogenation of 1-methyl decalin on Fe-Pt SAC with PDS = 1.49 eV were obtained for the most effective active sites for the enhanced electrochemical process. This study offers new possibilities for the catalytic dehydrogenation and hydrogenation of LOHC systems by highlighting the impact of doping on transition-metal-based catalysts.

Harnessing AEM electrolyzer-level performance through strategically designing the electronic structure of electrocatalysts, enabling dynamic functional switching - Kumar, Sonu; Verma, Tushar Singh; Selvaraj, Kaliaperumal (ACS Catalysis, 2025)
The anion exchange membrane water electrolyzer (AEMWE) is a promising technology for cost-effective hydrogen production. To promote its development and adoption, targeted efforts are focused on finding non-platinum group metal (non-PGM) electrocatalysts that efficiently facilitate the hydrogen evolution reaction (HER) and the oxygen evolution reaction (OER). Nickel sulfides (NiS) are effective OER catalysts; however, they suffer due to leaching-related instability at electrolyzer stack operational conditions. We introduce a rational non-PGM design that enhances stability during the OER while excelling at the HER, showcasing molecular-level insights for a scalable AEMWE zero-gap stack device. NiS coating is applied to the Al-metal-organic framework supported by 3D porous nickel foam (NSMA), leading to charge localization at the interface, which helps in OER by requiring only 322 millivolts at 100 mA cm-2. The main innovation in the NSMA design is a controlled electroreduction process that converts the Millerite phase into Ni3S2, a catalyst (rNSMA). This transformation leads to charge delocalization at the surface and a low overpotential of -80 mV at -100 mA cm-2 for the HER. In a full cell, this catalyst duo requires an overpotential of 1.49 V, outperforming the commercial Pt/Ru catalyst pair at 1.58 V. In a scaled-up 12.96 cm2 AEM electrolyzer single-cell stack, current density rose from 398 to 1062 mA/cm2, maintained for over 100 h at high temperatures, achieving 99% Faradaic efficiency and 100% hydrogen purity. The AEM electrolyzer cell shows a good energy efficiency of 45.50 kWh/kg and a cell efficiency of 86.59%. Detailed studies, including DFT analyses, revealed that electronic structure modification enhances charge delocalization, driving its impressive performance on an industrially significant scale.
Keywords: anion exchangemembrane water electrolyzer (AEMWE); charge transfer; density functional theory(DFT); HER; nickel sulfide; OER

Highly active and durable MNS bifunctional electrocatalysts for enhanced anion exchange membrane water electrolysis - Singh, Kailash; Yadav, Himanshu; Samdani, Kunda; Selvaraj, Kaliaperumal (Electrochimica Acta, 2025)
The development of non-platinum group metal (non-PGM) electrocatalysts with performance comparable to their noble metal counterparts remains a significant challenge for overall water splitting. In this study, we demonstrate the performance of an Anion Exchange Membrane (AEM) water electrolyzer using a bifunctional, non-PGM electrocatalyst: reduced graphene oxide (rGO)-encapsulated MoS2/Ni3S2 (MNS) grown on a nickel foam (NF) substrate. The rGO/MoS2/Ni3S2 (rGO-MNS) electrode was synthesized via a facile, single-step hydrothermal method. For the hydrogen evolution reaction (HER), the rGO-MNS electrode exhibited a low overpotential of 94 mV at a current density of 100 mA cm-2, maintaining excellent stability over 50 h with a minimal degradation rate of 120 mu V h-1. In the case of the oxygen evolution reaction (OER), an overpotential of 410 mV was required to reach the same current density, with a similarly robust durability and a degradation rate of only 360 mu V h-1. When employed as symmetric electrodes for overall water electrolysis, the rGO-MNS system achieved a current density of 10 mA cm-2 at a cell voltage of 1.51 V, outperforming the benchmark Pt/C & Vert;Ru/C catalyst pair, which required 1.58 V to reach the same performance. The enhanced electrocatalytic activity and durability are attributed to the conductive rGO encapsulation, which facilitates charge transfer and mitigates surface oxidation of the catalyst. These results present a promising strategy for designing cost-effective, durable, and highperformance non-PGM electrodes for AEM water electrolysis.
Keywords: Anion Exchange Membrane Water Electrolysis; Bifunctional Electrocatalyst; hydrogen evolution reaction; Oxygen Evolution Reaction; rGO-MNS

Material selection for enhanced performance in anion exchange membrane water electrolyzers: a study of membranes and gaskets - Singh, Kailash; Selvaraj, Kaliaperumal (Industrial & Engineering Chemistry Research, 2025)
Anion exchange membrane water electrolyzer (AEMWE) is an emerging technology for large-scale hydrogen production, where membrane electrode assembly (MEA) plays a critical role in the electrolyzer efficiency. This study investigates the effects of different membranes (Piperion, Aemion, and Sustainion) and gaskets (Viton, poly(tetrafluoroethylene) (PTFE), and Silicon) using a non-platinum group metal (non-PGM) bifunctional electrocatalyst under fixed compression and flow rates. Membrane properties such as ionic resistance and diffusion and gasket properties like thermal suitability and compressibility significantly affect the overall performance of AEMWE. The results indicate that Sustainion and Aemion membranes are best suited for lab-scale and industrial applications, respectively, while Silicon and PTFE gaskets are optimal for corresponding scales. Understanding these effects can help to improve the efficiency and guide material selection. This study provides valuable insights for researchers developing AEMWE technology, enabling advancements from laboratory research to megawatt-level industrial hydrogen production and supporting the transition to clean-energy solutions.

Rational design of hydrophobic Cu/CuO electrodes for electrochemical oxygenation of tetralin: a strategic approach - Cherukuthota, Sri Vidya; Mathew, Elizabeth; Verma, Tushar Singh; Joshi, Krati; Selvaraj, Kaliaperumal (ChemSusChem, 2025)
Electro-organic synthesis presents a sustainable and practical alternative to traditional organic synthesis methods, which typically utilize harsh reagents and require energy-intensive conditions. Nevertheless, the challenge of achieving satisfactory conversion and selectivity rates in electrocatalytic oxidation using a non-platinum group metal (PGM) catalyst pair still needs to be addressed. This study demonstrates the application of a non-PGM-based catalyst pair for the electrocatalytic oxidation of tetralin to 1-tetralone, a highly demanded raw material in the pharma industry. Copper electrodeposited on teflonated carbon paper combined with copper foam as the electrocatalyst pair has demonstrated impressive conversion and selectivity ratios to electro-synthesize 1-tetralone at room temperature and atmospheric pressure. The optimal choice of a non-PGM catalyst, ideal mass loading, and a unique electrode configuration resulted in an ultimate conversion of about 99% of tetralin and 1-tetralone selectivity -93.7%, yield -92.6%. The reaction pathway associated with the electrochemical phenomena is supported by first principles-based density functional theory calculations and X-ray photoelectron spectroscopy of the electrocatalyst. This process has exceptional performance that can be adapted for a wide range of substrates and is straightforward, ambient, reagent-free, scalable, and therefore beneficial for industrial use. Therefore, initiatives have been taken in this direction.
Keywords: C-H activation; Copper; electrochemical oxidation; non-PGM electrocatalysts; tetralin; Tetralone

Composite Sn-Fe oxide as a compatible OER electrocatalyst for electrochemical alkaline water electrolysis - Velluva, Abhijai; Christi, Darren Sebastian; Selvaraj, Kaliaperumal (Journal of Physical Chemistry C, 2026)
Green hydrogen production through electrochemical water splitting is one of the optimal replacements for conventional fossil fuel energy sources. The development of highly active and electrochemically stable non-noble-metal electrocatalysts for the sluggish oxygen evolution reaction (OER) is considered to be an important step in decreasing the energy requirement during alkaline water electrolysis. Herein, we report a Sn-doped FeOx composite (SnFeOx) powder, which could be synthesized through a single-step hydrothermal method and is reported for the first time for OER during electrochemical water electrolysis. SnFeOx exhibits a low eta(100) (overpotential at 100 mA cm(-2) current density) value of 288 mV and a good Tafel slope of 35 mV dec(-1) in 1 M KOH, which surpasses the performance of standard non-PGM OER catalysts. A long-durability test at a higher current density of 100 mA cm(-2) for 50 h reveals the excellent activity retention of SnFeOx (>99%). The suitability of SnFeOx for full-water splitting was tested with Pt/C as a cathode electrode, and Pt/C/NF||SnFeOx/NF exhibited a lower eta(10) value of 1.56 V that is superior to Pt/C/NF||Ru/C/NF (1.59 V) with more than 99% retention at a current density of 10 mA cm(-2) for 50 h. The more favorable OER performance of SnFeOx compared to FeOx can be attributed to the successful Sn4+ doping along with increased oxygen defective sites and larger electrochemical surface area.

Integrated cell engineering and scale-up of a non-PGM bifunctional electrocatalyst for durable AEM water electrolysis - Singh, Kailash; Kavitha, T.; Selvaraj, Kaliaperumal (Sustainable Energy & Fuels, 2026)
Developing a scalable and sustainable non-Platinum Group Metal (non-PGM) bifunctional electrocatalyst for Anion Exchange Membrane (AEM) water electrolyzers remains a significant challenge, particularly at industrially relevant scales. Most reported non-PGM catalysts are demonstrated on small electrode areas (typically <= 2 cm(2)), making scalability a major bottleneck. Issues such as achieving uniform catalyst coating, maintaining similar structural morphology, and preventing activity loss due to leaching become increasingly prominent at larger scales. Therefore, a Nickel Copper Phosphide-Nickel Sulphide (NCP-NS) catalyst was developed and successfully scaled-up to >10 cm(2) electrode active area, and its performance was evaluated in an electrolyzer cell. A larger 13 cm(2) AEM cell was developed by addressing key parameters: (i) electrode design (mass loading density), (ii) assembly conditions (torque and gasket thickness), (iii) operational parameters (flow rate and temperature), and (iv) engineering aspect measurements (Fujifilm pressure distribution and interfacial contact resistance). These optimizations resulted in a high current density of 1012 mA cm(-2) at 2 V, with the stack maintaining 98% of its performance after 100 hours of continuous operation. The electrocatalysts delivered 55.96 kWh kg(-1) energy efficiency at 2 V. This work demonstrates how systematic scale-up and cell engineering can bridge the gap between lab-scale innovation and commercial application.

Strategic design of strained heterostructure anode for large-area AEM water electrolyzer via a facile etching method - Kumar, Sonu; Selvaraj, Kaliaperumal (ACS Applied Energy Materials, 2026)
Iron-based doped catalysts and various heterojunctions have been extensively studied for the Oxygen Evolution Reaction (OER). However, our understanding of the structural properties of these catalysts remains limited. Additionally, most studies have been conducted on a small scale, which restricts their practical application and potential. In this work, we designed an interface composed of Fe-doped Ni3S2 and FeOOH (FNS/NF) to function as an anode for a larger-area Anion Exchange Membrane Water Electrolyzer (AEMWE) cell. This was accomplished using the electrodeposition and electroless deposition methods at room temperature. The FNS/NF anode achieves a current density of 1 A cm-2 when paired with a standard catalyst (Pt/C) cathode, outperforming current state-of-the-art configurations that reach only 0.91 A cm-2. Furthermore, the FNS/NF anode attains over 1.3 A cm-2 when combined with our already published nonprecious metal cathode (rNSMA). This configuration exhibits a degradation rate of 1.2 mV/h after more than 100 h of stability testing, accompanied by an impressive cell efficiency of 85.40% and an energy efficiency of 38.98 kWh/kg. Comprehensive characterizations were conducted to gain a deeper understanding of the catalyst's phase characteristics, revealing that iron is in the +3 oxidation state in both FeOOH and Fe-doped Ni3S2, which forms a heterojunction. The FeOOH on the surface helps reduce the overpotential, while the Fe-doped Ni3S2 sustains performance for a longer duration.
Keywords: AnionExchange Membrane Water Electrolyzer (AEMWE); Compressive Strain; interface; Iron Oxyhydroxide; Iron-doped Nickel Sulfide; OER